A spatially explicit definition of conservation priorities according to population resistance and resilience, species importance and level of threat in a changing climate. Issue 7 (27th April 2017) - Brambilla, Mattia; Caprio, Enrico; Assandri, Giacomo; Scridel, Davide; Bassi, Enrico; Bionda, Radames; Celada, Claudio; Falco, Riccardo; Bogliani, Giuseppe; Pedrini, Paolo; Rolando, Antonio; Chamberlain, Dan
Abstract: Aim: Human‐induced climate change requires conservation strategies incorporating its potential effects on species and communities. Key components of population persistence can be attributed to resistance (the capacity to remain unaffected) or resilience (capacity to absorb and recover) to climate change. In situ climatic refugia can act as resistant distribution units, and ex situ climatic refugia and the corridors to reach them may enhance resilience. We develop a novel approach selecting conservation priorities, resistant units and resilient areas according to structural connectivity and future distribution, to identify strategies that maximize the chances of species persistence in a changing climate. Location: Italian Alps. Methods: Conservation priorities were defined across species according to the regional conservation status and the level of threat from climate change, and across sites according to their suitability for target species and their related potential for population persistence (in situ climatic refugia, i.e., resistant units) or redistribution (ex situ climatic refugia and main corridors according to current and future connectivity, i.e., resilient units). Results: Models suggested a marked loss of suitable area for all species by 2050 (ranging from 50% for pygmy owl and water pipit, to 84% for snowfinch in the worst scenario), and a general loss of connectivity, which was particularly marked for pygmy owl and snowfinch. The approach applied to Alpine birds of different habitats led to a spatially explicit definition of conservation priorities. Main conclusions: The spatial definition of conservation priorities according to species (regional importance and level of threat), resistance and resilience refines the definition of management/conservation priorities (including protected area definition), complementing the existing approaches to address climate change‐induced threats in planning conservation and ecological networks.